Marketed surplus of Indonesian rice production - Amzul Rifin (Cogent Economics & Finance)
Indonesian rice production has exhibited a positive increasing trend over the years. On the other hand, rice retail prices tend to fluctuate, even though the country has imported rice. One reason for this is that not all of the rice produced is sold to the market or marketed surplus. The objective of this study is to analyse the marketed surplus of Indonesian rice production and its determinants. The rice farmers’ survey conducted by Statistics Indonesia in 2014 was utilised. The Heckman two-step procedure was utilised to address the sample selectivity bias. The results indicate that the rice marketed surplus in Indonesia was 50 percent, with the highest in Java at 57percent, while outside Java, the marketed surplus was 48 percent. From the variables analysed, three variables were significant, and the sign was consistent among locations. Meanwhile, the output price has different effects on the three locations.